Near ultraviolet excitable cyan-green phosphors of Ba6La2Al3ScO15:Ce3+ and Ba6La2Al3ScO15:Ce3+, Tb3+: investigations on the crystal structure, site assignment of Ce3+ and Tb3+ ions, and an energy transfer process from Ce3+ to Tb3+. Issue 16 (28th March 2023) - Iwaki, Masato; Onodera, Mizuho; Uematsu, Kazuyoshi; Toda, Kenji; Sato, Mineo
Abstract : An energy transfer from Ce 3+ to Tb 3+ is feasible in energy transition processes for the development of optical devices, especially phosphor-converted white LEDs (pc-wLEDs). Abstract : An energy transfer from Ce 3+ to Tb 3+ is feasible in energy transition processes for the development of optical devices, especially phosphor-converted white LEDs (pc-wLEDs). Most of the energy transfer phosphors co-doped with Ce 3+ and Tb 3+, unfortunately, have weak absorption under a near-ultraviolet light of around 405 nm and blue light excitation, making them incapable for use as near ultraviolet or blue LEDs. In this study, novel energy transfer luminescent materials, Ba6 La2 Al3 ScO15 :Ce 3+, Tb 3+, isostructural with existing Ba6 La2 (Al, Fe)4 O15, were successfully synthesized through a conventional solid-state reaction as a single phase. The phosphors showed a broad cyan emission of Ce 3+ and narrow green emissions of Tb 3+ under a near-ultraviolet light of 405 nm, which was nearly located at an emission wavelength of near-ultraviolet LEDs. The occurrence of energy transfer from Ce 3+ to Tb 3+ was evidenced by emission lifetime measurements. The lifetime analysis based on formulated energy transfer models, such as Inokuti–Hirayama, Yokota–Tanimota and Martin models, revealed that an energy transfer process from Ce 3+ to Tb 3+ took place dominantly by a dipole–dipole interaction with low migration among the donors of Ce 3+ .